Sovereign CDS contagion in the European Union: a multivariate GARCH-in-variables analysis of volatility spill-overs - Oliveira, Maria Alberta (2014)
GARCH-with-variables model is used to assess volatility contagion in the Eurozone Debt Crisis. Credit Default Swaps on sovereign debt with 3 years maturity are used as a reference financial instrument, covering the sample period from 2008-2013. Daily data on Credit Default Swaps is used. We conclude that there is strong statistical evidence of volatility contagion in CDS spreads from the Eurozone periphery to its core. However, the direction of contagion is contingent on the periphery and core countries being assessed. As such, German 3 year CDS on sovereign debt mean equation is to vulnerable to Portuguese and to Greek CDS volatility, whilst German sovereign CDS volatility is vulnerable to greek one day lagged sovereign volatility. Differently, France’s sovereign debt Credit Default Swaps are only exposed to Spanish and Italian sovereign CDS in the mean equation. Exposure to greek lagged one day volatility exists as well.